ABANDONED HOUSING PROJECTS IN MALAYSIA: TO ENFORCE THE EXISTING LAWS OR INTRODUCE NEW LAWS? - Hua Siong Wong; Norazuan binti Amiruddin; Azwina Wati binti Abdull Manaf; Hafiza binti Abdul Razak (Journal of Islamic, Social, Economics and Development, 2022)
Abandoned housing project is a global issue and it happens in Malaysia too. This issue will bring negative impact to the stakeholders, environment and economic. In Malaysia, the government is still not able to resolve this issue although they are numerous laws and policies have been introduced and implemented by the Malaysian government. Thus, the main question is to what extend the existing laws and policies implemented by the Malaysian government has successfully reducing the abandoned housing projects. The objectives of the study are to examine the existing laws and policies and to examine whether a better legal framework should be proposed in overcoming the issues of abandoned housing projects in Malaysia. This is qualitative study and not an empirical study. The data was collected by library-based research from various primary and secondary data sources, including case laws in Malaysia, written statutes, publication of journal and article. It is suggested that the existing laws are used to their full capacity by the enforcers in order to overcome the existing abandoned housing project issues faced by the public.